Exploring strategic factors for promoting blood donation campaign / Nur Shahrulliza Muhammad … [et al.] - Muhammad, Nur Shahrulliza; Hamdan, Fairus; Norman, Helmi; Yunus, Amie Azida (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
Approximately 2.2 percent of the Malaysian population donates blood each year, compared to the standard expectation of 5 percent. It is a sign that this country will experience insufficient blood supply in the future. This worrying statistic has led to the exploration of blood donation decision-making conducted worldwide for the purpose to understand the factors that will help to encourage the publics to donate blood. Understanding the intention-based Theory of Planned Behavior (TPB) helps the researchers to develop targeted campaigns based on specified factors from the pool survey. These TPB factors among Malaysian adults have not yet been fully investigated. Thus, the survey was administered to respondents concerning potential motivating factors based on the suggested TPB elements in their decision to donate blood. The study was conducted on Malaysian adults working in the public and private sectors. This study was to identify the correlation and regression value to identify the relationship between the factors and to infer causal relationships between the factors. The result shows that there is a significant relationship between the subjective norms with the blood donation intention. The potential discouraging factors need to be addressed to ensure future decision whether or not to donate blood might be inflected. However, this study has pointed out for further investigation on factors affecting the donor intention and decision to donate the blood among Malaysian adults.